2016
DOI: 10.1111/cch.12363
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related impairments in young children with ADHD: a community‐based study

Abstract: Young children with ADHD experience a number of health-related impairments, which are exacerbated by the presence of internalizing and externalizing co-morbidities. Clinicians should consider the broader health of children with ADHD in clinical consultations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Grünwald and Schlarb (2017) also noted higher comorbid occurrence of insomnia and nightmares in this sub group (6–13 years, n = 72). Subjective reports by parents revealed higher prevalence of sleep problems in children with ADHD combined presentation (30%) as compared to ADHD inattentive presentation (17%), however this finding was not statistically significant (Sciberras et al, 2016). However, in a previous study by Hansen et al (2011), ADHD combined and hyperactive subtype ratings did not differ from ADHD inattentive on the CSHQ scale (7–13 years, n = 39).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Grünwald and Schlarb (2017) also noted higher comorbid occurrence of insomnia and nightmares in this sub group (6–13 years, n = 72). Subjective reports by parents revealed higher prevalence of sleep problems in children with ADHD combined presentation (30%) as compared to ADHD inattentive presentation (17%), however this finding was not statistically significant (Sciberras et al, 2016). However, in a previous study by Hansen et al (2011), ADHD combined and hyperactive subtype ratings did not differ from ADHD inattentive on the CSHQ scale (7–13 years, n = 39).…”
Section: Resultsmentioning
confidence: 84%
“…Using the CSHQ, it was also found that elevated scores on individual subscales (sleep onset latency, night waking, daytime sleepiness, sleep duration, parasomnias, daytime sleepiness) among the ADHD cohort were positively associated with a variety of parent reported externalizing behavioral problems (social, attentional and disruptive behaviors) and functional impairment (family, school, life skills, social activities and risky actions) (Aronen et al, 2014; Choi et al, 2010; Eyuboglu & Eyuboglu, 2018). Additionally, subjective reports by parents revealed that sleep problems emerging early for children (aged 6–8 years) with ADHD ( n = 177) are uniquely associated with co-occurring internalizing and externalizing behaviors (Sciberras et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…With core symptoms of inattention and/ or hyperactivity-impulsivity, ADHD is a chronic condition that interferes with an individual's functioning (American Psychiatric Association AP, 2013). Associated health and behavioural issues are also common, including poor overall health (Sciberras et al, 2016), conduct problems, anxiety and depression (Angold, Costello, & Erkanli, 1999;Biederman et al, 2006). When experienced in childhood, ADHD adversely impacts the family system (Johnston & Mash, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…15 Children with ADHD and co-occurring internalising/externalising behaviour disorders are prone to health-related impairments. 16 Children with ADHD and comorbid externalising behaviour disorder have poorer social skills than those with ADHD alone. 17 There is limited information on functional impairment in young children with ADHD in Thailand.…”
Section: Resultsmentioning
confidence: 99%